Analizar la dependencia de la afluencia en redes sociales en tiempo de post- pandemia en la ciudad de Quevedo de la Parroquia San Camilo - Choez Carranza, Jorge Ariel (2021)
Networks are currently very useful for young adults and children to keep informed; However, it has created a dependency especially for the inhabitants of the El Mango sector of the San Camilo Parish, apart from what has caused the covid19 pandemic in the last three years. To do this work we use inductive and deductive methods for the collection of informational data from the community, it was carried out through the interview applying what the survey is, obtaining a reality that parents do not have knowledge about the influx of young people and kids. Not only in this sector is this new reality lived, but throughout our country, many of the users, both children, young people and adults, do not have a true teaching of the use of social networks since false news is promoted in this sector, and allow users to interact with published content with others. So making a general summary of the Analysis of the influx in social networks I can say that in many families there is 90% ignorance of what social networks offer that can be done and that cannot be done when we become users.